School Cartography And Cartographic Literacy: Conceptions For Teaching Geography. - Silva, Allanis (2023)
The present work arises in the context of the studies developed in the Group of Research, Teaching and Extension of Alfabetização Geográfica (ALFAGEO) of the Universidade Estadual do Ceará (UECE), linked to the Laboratório de Prática de Ensino de Geografia (LAPEGEO/UECE) in order to contribute with the theoretical development through the bibliographic survey of the authors who approach the presented theme. In the text, the history of cartography in Brazilian geographic teaching will be approached, the map as a technical, methodological and language tool to learn Geography, in addition to the process of cartographic literacy as a primordial methodology for the teaching and learning process of school cartography. This research was elaborated through a bibliographic survey of works that discuss school cartography in the context of cartographic literacy.